State of the system Xbox360.
The GamePros share the Xbox360 games they've been engrossed in lately.
Keywords: Xbox 360 (Video game console); NBA JAM (Game); Call of Duty; Rock Band3.; Red Dead Redemption; Gears of War 2.; Mass Effect 2.